1913 Or. Laws 433, ch. 232,§§ 22. - (:unkn) unknown (My University, 1913)
It shall be unlawful at any time in the State of Oregon to shoot or discharge any gun at any game bird or game animal from, or while upon any railroad right of way, or any public road or highway.
Keywords: HUNTING REGULATION